IMPLEMENTASI PSAK NO. 45 PADA PONDOK PESANTREN ASSALAM PONTIANAK - B51108127, Wendy Aprilianti (Jurnal KIAFE, 2014)
The nonprofit organization is an organization that gives services to the public in order to increase the quality of human life and established not for profit only. Nonprofit organizations rely on income from donations to carry out its service activities. In a way, nonprofit organization dedicated to the presentation of financial statements so that contributors know the source as well as how to use existing resources in the organization. Indonesian Institute of Accountants (IAI) to anticipate the development of non-profit organizations in Indonesia by issuing a Statement of Financial Accounting Standards of PSAK No. 45 on "Financial Reporting of Non-Profit Organizations". With the implementation of PSAK organizations is expected to manage your financial information in a more professional and the resulting information to be more qualified. The financial statements presented are statements of financial position, statement of activities, statement of cash flows, and notes to the financial statements. Type text or a website address or translate a document. Cancel Translate from: Malay But in reality, most of the non-profit organizations in Indonesia have not been present its financial statements in accordance with of PSAK 45. One of them is a Boarding School Assalam Pontianak. Pondok Pesantren Assalam Pontianak is a non-profit organization that moves in education, with priority giving proper education to santriwan / wati from junior level and MA with emphasis on religious education Islamic Shari'a. Pondok Pesantren Assalam Pontianak financial statements present only an outline of the registering the income and expenditure for the cost of school activities. Financial statements have not been implemented PSAK 45. Based on the above, the authors are interested in implementing of PSAK 45 on "Financial Reporting of Non-Profit Organizations" in Pondok Pesantren Assalam Pontianak and the writer wants to know what factors are causing Boarding School Assalam Pontianak not apply of PSAK 45. The analytical tool used is a qualitative analysis that is required under SFAS 45 in the implementation of its financial statements and questionnaires to determine the factors causing Boarding School Assalam Pontianak not use of PSAK 45. Authors apply of PSAK 45 in Pontianak Assalam Boarding School for financial statements from January 2012-December 2012. Based on the analysis it can be concluded that the Pondok Pesantren Assalam Pontianak in the presentation of its financial statements to apply of PSAK 45 although it is very simple. In addition it can be seen that three factors influence the adoption of of PSAK 45 has not been on Boarding School assalam Pontianak is: (a) Boarding School Assalam Pontianak possessed its own financial reporting standards are made ​​simple. (b) The cottage pesantrean Assalam Pontianak not know about PSAK No. 45. (c) The absence of a requirement required under PSAK No.45.